Infestation of Coffee White Stem Borer Xylotrechus quadripes (Coleoptera: Cerambycidae) In Bolaven Plateau, Southern Laos - Phewphanh, Phonepadith; Rattanalrasy, Souphaphone; Chouangthavy, Bounsanong (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
Xylotrechus quadripes (Chevrolat), the Coffee White Stem Borer, is a major pest of arabica coffee plantations (Coffea arabica L.) in southern Laos and some Asian countries. This study was conducted on an arabica coffee plantation in Bolaven Plateau, southern Laos, during January, March and June 2021. The study was undertaken to assess the number of adult beetles, larvae and their exit holes of the Coffee White Stem Borer, or X. quadripes, as well as their relationship. The result indicated that there was a significant difference in the number of adults depending on the collection date; moreover, the number of adults gradually increased from January to June. However, there was no significant difference between the number of larvae and exit holes for the collection date. On the whole, there was a relatively strong positive relationship between the number of adults and larvae versus the number of exit holes. This finding was the fundamental data to support the farmer in terms of properly controlling and managing their coffee plantations in the region.